2003
DOI: 10.1136/fn.88.5.f371
|View full text |Cite
|
Sign up to set email alerts
|

Urine polymerase chain reaction as a screening tool for the detection of congenital cytomegalovirus infection

Abstract: Objectives: To define the incidence of congenital cytomegalovirus (CMV) infection in a defined population in Israel as diagnosed by urine polymerase chain reaction (PCR), and to assess the utility of this method for screening for congenital CMV infection. Design: A convenient sample of urine specimens from asymptomatic newborns were subjected to CMV PCR. Positive results were validated by urine tube culture and by determination of serum CMV IgM antibodies. Maternal CMV IgG was determined in a representative sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 18 publications
0
30
0
4
Order By: Relevance
“…CMV PCR of a urine sample obtained on DOL 12 almost certainly excluded the possibility of congenital infection, given the known sensitivity and specificity of urine PCR for the diagnosis of congenital CMV. 21,27 Despite an initial absence of symptoms, this infant' s systemic viral load continued to rise to 4.8 log 10 genomes/mL on DOL 21 (the last day that DBS samples were available through the immunoreactive trypsinogen study protocol). Although no samples were available to test for CMV DNA between DOL 21 and DOL 33, the viral load on DOL 33 when the patient demonstrated a CMV sepsis syndrome and required surgical intervention for NEC was ∼6 log 10 genomes/mL.…”
Section: Figurementioning
confidence: 99%
“…CMV PCR of a urine sample obtained on DOL 12 almost certainly excluded the possibility of congenital infection, given the known sensitivity and specificity of urine PCR for the diagnosis of congenital CMV. 21,27 Despite an initial absence of symptoms, this infant' s systemic viral load continued to rise to 4.8 log 10 genomes/mL on DOL 21 (the last day that DBS samples were available through the immunoreactive trypsinogen study protocol). Although no samples were available to test for CMV DNA between DOL 21 and DOL 33, the viral load on DOL 33 when the patient demonstrated a CMV sepsis syndrome and required surgical intervention for NEC was ∼6 log 10 genomes/mL.…”
Section: Figurementioning
confidence: 99%
“…This might be due to the undetectable amount of CMV-IgM antibodies in cord blood by the method used, the insensitivity of CMVIgM measurement in detecting congenital CMV infection [10], and/or delayed development of CMVIgM in infected fetuses [2].…”
Section: Discussionmentioning
confidence: 99%
“…All the urine specimens were processed and used for CMV PCR reaction as recently described by our group in details. 13 In that study we have shown the high sensitivity and specificity of the PCR assay. In a prestudy sensitivity assay, the PCR reaction was positive in 99 of 100 urine specimens (99% sensitivity) spiked with as low as 20 to 30 viral copies/reaction.…”
Section: Methodsmentioning
confidence: 99%